The Long History of Geosynthetics Use on Forest Roads. Issue 1 (January 2015) - Keller, Gordon; Berry, Jonathan
Geosynthetics have been used in a wide range of applications on forest roads over the past 40 years. Some of the earliest uses involved reinforcement in simple walls, drainage or filtration in geocomposite underdrains, and subgrade stabilization. These early efforts were typically experimental. Geosynthetic application over time became better defined by function, and use was specified for drainage, filtration, separation, or reinforcement. Road uses were typically in underdrains to keep a granular filter material clean, for separation over soft subgrade soils to keep aggregate from becoming contaminated, as reinforcement layers within a mechanically stabilized earth retaining wall or reinforced fill, and as interlayers within a pavement. Today geosynthetic use is more sophisticated and better defined: materials for each function have specific strength and durability properties appropriate for their use. New combinations of materials have resulted in drainage geocomposites, multilayer filters, geogrids with geotextiles, geofoam, and geocells. Many applications in erosion control, as well as other creative uses, have also been developed. Today, more attention is given to quality control and properties testing to better characterize the materials. Although use of geosynthetics has gained wide acceptance in many sectors of civil engineering and highway construction, it is still limited on forest roads. This paper documents the evolution of geosynthetics' use on forest roads, highlights current creative and cost-effective applications of geosynthetics, and promotes geosynthetics in the construction of low-volume roads.